Timing of gene expression in a cell-fate decision system - Aymoz Delphine; Solé Carme; Pierre Jean-Jerrold; Schmitt Marta; de Nadal Eulalia; Posas Francesc; Pelet Serge (University of Dundee, 2018)
During development, morphogens provide extracellular cues allowing cells to select a specific fate by inducing complex transcriptional programs. The mating pathway in budding yeast offers simplified settings to understand this process. Pheromone secreted by the mating partner triggers the activity of a MAPK pathway, which results in the expression of hundreds of genes. Using a dynamic expression reporter, we quantified the kinetics of gene expression in single cells upon exogenous pheromone stimulation and in the physiological context of mating. In both conditions, we observed striking differences in the timing of induction of mating-responsive promoters. Biochemical analyses and generation of synthetic promoter variants demonstrated how the interplay between transcription factor binding and nucleosomes contribute to determine the kinetics of transcription in a simplified cell-fate decision system.
Keywords: morphogens; cell-fate; gene expression; transcription; mating pathway; budding yeast